Pendidikan Karakter di Era Digital: Tantangan dan Strategi - Hilda Melani Purba; Humairoh Sakinah Zainuri; M. Falih Daffa; Nurhafizah Nurhafizah; Yunita Azhari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Character education in the digital era faces various complex challenges. Rapid advances in technology mean that children spend more time in cyberspace, such as playing games and social media, rather than opening learning sites. In this research, the method used is a qualitative descriptive method with literature study. The research results show that there are several challenges to character education in the digital era, including balance aspects, safety and security aspects, cyberbullying aspects, and copyright aspects. In overcoming these challenges, strategies that can be used are digital education, parental involvement and supervision, limiting screen time, and encouraging social interaction.